Intramolecular interaction of NEP regulated by CRM1 ensures the unidirectional transport of M1 for the nuclear export of influenza viral ribonucleoprotein - Hirohama, Mikako; Yamashita, Shun; Asaka, Masamitsu N.; Kuroki, Takahiro; Kawaguchi, Atsushi (Frontiers in Virology, 2023)
The influenza virus genome consists of single-stranded RNAs and forms viral ribonucleoprotein (RNP) complexes. After viral genome replication in the nucleus, the viral RNP interacts with viral protein M1. The M1-viral RNP complex is exported to the cytoplasm via the CRM1-dependent pathway using NS2/NEP as an export adaptor protein. NEP is a 14 kDa protein and diffusely localizes in the nucleus and cytoplasm. Upon binding to the NLS motif of M1, NEP inhibits the nuclear accumulation of M1 and promotes the nuclear export of M1-viral RNP complex. However, the detail mechanism by which NEP binds to M1 only in the nucleus remains unclear. Here, we found that the intramolecular interaction of NEP inhibits the interaction of NEP with M1. The intramolecular interaction of NEP was mediated through the interaction of the N-terminal NES motif with the M1binding domain at the C-terminus. By adding leptomycin B, a potent inhibitor of CRM1, the interaction of NEP with M1 was impaired. These results suggest that CRM1 disrupts the intramolecular interaction of NEP by recognizing the NES motif at the N-terminus of NEP, thereby promoting the interaction of NEP with M1. We also found that NEP mutant deficient in the intramolecular interaction was colocalized with M1 at the plasma membrane and did not show nuclear localization with M1. Based on these results, we propose that the intramolecular interaction of NEP regulated by CRM1 ensures the unidirectional transport of M1.